Implementation Kolmogorov-Smirnov Method on Queue System Simulation - Halifia Hendri; Sarjon Defit; Mardison (Universitas Putra Indonesia YPTK Padang, 2021)
Long queue always happen as main problem in re-registration of new students who passed the New Registration Student (NRS). The long queue makes the queueing system crowded and cannot be controlled properly. This research is aimed in knowing the model, process simulation model and how to use the method of Kolmogorov-Smirnov of system for re-registration of new students. The method is suitable on how to solve long queue system with new model and simulation. The proposed method is implemented in Senior High School in Padang, West Sumatera, Indonesia. The result of this research shows that after we divided queuing post 1 into two sub-posts namely post 1a and 1b on the first day and we note that average long applicants waiting at post 1a and 1b are smaller i.e. 2.3 minutes and 2.8 seconds as previously for 15 minutes. Furthermore, we divided queuing post 2 into 2 sub-posts namely post 2a and 2b on first day note that average long applicants wait at post 1a and 1b are smaller i.e. 0.2 minutes and 0.2 minutes as previously for 32 minutes. It can be concluded that the solution to the registration posts can make an average registration time waiting to be smaller.